MiR393 regulation of auxin signaling and redox-related components during acclimation to salinity in Arabidopsis - Iglesias, M.J. (2014)
One of the most striking aspects of plant plasticity is the modulation of development in response to environmental changes. Plant growth and development largely depend on the phytohormone auxin that exerts its function through a partially redundant family of F-box receptors, the TIR1-AFBs. We have previously reported that the Arabidopsis double mutant tir1 afb2 is more tolerant to salt stress than wild-type plants and we hypothesized that down-regulation of auxin signaling might be part of Arabidopsis acclimation to salinity. In this work, we show that NaCl-mediated salt stress induces miR393 expression by enhancing the transcription of AtMIR393A and leads to a concomitant reduction in the levels of the TIR1 and AFB2 receptors. Consequently, NaCl triggers stabilization of Aux/IAA repressors leading to down-regulation of auxin signaling. Further, we report that miR393 is likely involved in repression of lateral root (LR) initiation, emergence and elongation during salinity, since the mir393ab mutant shows reduced inhibition of emergent and mature LR number and length upon NaCl-treatment. Additionally, mir393ab mutant plants have increased levels of reactive oxygen species (ROS) in LRs, and reduced ascorbate peroxidase (APX) enzymatic activity compared with wild-type plants during salinity. Thus, miR393 regulation of the TIR1 and AFB2 receptors could be a critical checkpoint between auxin signaling and specfic redoxassociated components in order to coordinate tissue and time-specific growth responses and tolerance during acclimation to salinity in Arabidopsis.